Facile and efficient synthesis of xanthenedione derivatives promoted by niobium pentachloride - Santos, Willian H. dos [UNESP]; Silva-Filho, Luiz C. da [UNESP] (Springer, 2016)
Xanthenedione derivatives were synthesised in one-pot reactions between arylaldehyde derivatives and 1,3-cyclohexanedione promoted by niobium pentachloride. This new method is simple, costeffective, high-yielding with a good variety of substrates generality, and can be conducted within reasonable reaction times. (C) 2016 Institute of Chemistry, Slovak Academy of Sciences
Keywords: niobium pentachloride; Lewis acid; xanthenedione derivatives; one-pot reactions